Sunday

April 20, 2014

April 20, 2014

Posted by **Isaac** on Tuesday, April 7, 2009 at 6:14pm.

- math -
**drwls**, Tuesday, April 7, 2009 at 6:32pm2a^2 + 8a = -12

a^2 + 4a + 6 = 0

a = (1/2)*[-4 +/- sqrt(16-24)]

= (1/2)*[-4 +/- 2i sqrt2]

where i = sqrt(-1)

**Related Questions**

Math - Simplify 2a^2 b^3 (4a^2 + 3ab -ab) A.) 8a^4 b^5 + 3a^3 b^5 - 2a^3 b^4 B...

Sally - I have a factoring question; what is 8a^2-8a-30? I've been working on ...

algebra 2 multiple choice HELP - find f(a), if f(t) = 2t2(squared)-t-2 A. 2(a+t)...

maths - If A=1+r^a+r^2a+r^3a+.......................to infinity B=1+r^b+r^2b...

MATH DUDES!!! - I have 3 questions. 1.whats the value for h in 12h+9=85? 2.whats...

Math situation - please help me solve Multiply and simplify type exponential ...

Math...help - remove the brackets and simplify questions a) 3(2a+5)+2(a+7) b) 5(...

Math - Which expression is equivalent to (-2)(a+6)? -2a+6 2a+12*** -2a-12 -2a+12...

Math - Find the equation of a hyperbola of the form x squared / M - y squared / ...

Math11U - A Pythagorean Triple is a set of integers that satisfy the Pythagorean...